Diagnostic accuracy of DIPSI criteria for diagnosing gestational diabetes mellitus in Puducherry - S Pravinraj; Mohamed M. Tajudeen; Darshana Zala; Rajini Senthil; Mercy M. Jafrin (Journal of Family Medicine and Primary Care)
Context: Gestational diabetes mellitus (GDM) is a major concern in recent years. During pregnancy, it is difficult to consume 75 g of glucose in the fasting state as pregnant women may experience symptoms such as vomiting. The Diabetes in Pregnancy Study Group India (DIPSI) criterion requires a single prick in the non-fasting state to collect the sample for diagnosing GDM. Aims: This study aimed to assess the diagnostic accuracy of DIPSI criteria compared to the WHO criteria for GDM diagnosis. Settings and Design: A community-based cross-sectional study was conducted among pregnant mothers attending the primary health centers in Puducherry from August 2022 to November 2022. Methods and Material: A total of 384 samples were selected, and 75 g of anhydrous glucose was given after 8 hours of overnight fasting. Both fasting and postprandial venous blood sugar levels were measured to determine the prevalence of GDM as per the WHO 2013 criteria. After 2 days, GDM was diagnosed among all study participants based on the DIPSI criteria. Further analysis was done. Results: The prevalence of GDM was 14.1% and 12.8% per the WHO 2013 and DIPSI criteria, respectively. In comparison to the WHO 2013 criteria, DIPSI had 79.63% sensitivity, 98.18% specificity, 87.76% positive predictive value, and 96.72% negative predictive value. The results of kappa statistics showed that there was almost perfect agreement between the WHO 2013 criteria and DIPSI criteria. Conclusions: The present study shows that the DIPSI criteria can be used to screen and diagnose GDM as there is no need for overnight fasting. The blood glucose value can be measured easily with a single prick, which is comfortable for both pregnant women and treating doctors.